AUF-1 knockdown in mice undermines gut microbial butyrate-driven hypocholesterolemia through AUF-1–Dicer-1–mir-122 hierarchy - Das, Oishika; Kundu, Jayanta; Ghosh, Atanu; Gautam, Anupam; Ghosh, Souradeepa; Chakraborty, Mainak; Masid, Aaheli; Gauri, Samiran Sona; Mitra, Debmalya; Dutta, Moumita; Mukherjee, Budhaditya; Sinha, Surajit; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction and objective Cholesterol homeostasis is a culmination of cellular synthesis, efflux, and catabolism to important physiological entities where short chain fatty acid, butyrate embodied as a key player. This discourse probes the mechanistic molecular details of butyrate action in maintaining host-cholesterol balance. Methods Hepatic mir-122 being the most indispensable regulator of cholesterol metabolic enzymes, we studied upstream players of mir-122 biogenesis in the presence and absence of butyrate in Huh7 cells and mice model. We synthesized unique self-transfecting GMO (guanidinium-morpholino-oligo) linked PMO (Phosphorodiamidate-Morpholino Oligo)-based antisense cell-penetrating reagent to selectively knock down the key player in butyrate mediated cholesterol regulation. Results We showed that butyrate treatment caused upregulation of RNA-binding protein, AUF1 resulting in RNase-III nuclease, Dicer1 instability, and significant diminution of mir-122. We proved the importance of AUF1 and sequential downstream players in AUF1-knock-down mice. Injection of GMO-PMO of AUF1 in mouse caused near absence of AUF1 coupled with increased Dicer1 and mir-122, and reduced serum cholesterol regardless of butyrate treatment indicating that butyrate acts through AUF1. Conclusion The roster of intracellular players was as follows: AUF1-Dicer1-mir-122 for triggering butyrate driven hypocholesterolemia. To our knowledge this is the first report linking AUF-1 with cholesterol biogenesis.